Fatores explicativos dos conflitos internacionais relacionados a segurança energética do petróleo - Silva, Emylle Cristine Alves e (Universidade Federal Rural do Semi-Árido, 2020)
Nowadays, oil is a component of the energy matrix of extreme global importance, being the reason for geopolitical conflicts in the countries which have its possession and those that have not. Thus, the energy security for this oil must be taken into account in each country which produces or consumes it. Granting that fluctuations in oil price on the market do not bring future consequences for those countries. However, the interdependence between exporting and importing countries, together with conflicts (political, strategical and socioeconomical) had made their energetic security even more difficult. As a result, many countries, especially those that do not present well-founded policies, went into crisis and had to change their policies in order to deal with debts and their dependence on the product. In Brazil, oil brought with it an incentive to fight for it to be nationalized, preventing foreign companies from taking what is theirs, thus Brazil had its moments of crisis and, soon after, its development. The current paper has as goals to explore some of the referred conflicts at cited countries as well as describe its policies for energetic security.
Monografia
Keywords: Conflitos; Países exportadores e importadores; Brasil; Conflicts; Exporting and importing countries; Brazil; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA